Man-made lowlands : - Ven. G.P. van de (Uitgeverij matrijs, 1996)
Man-made lowlands is the standard book on the history of water management and land reclamation in the Netherlands. Among others, attention is being paid to the Middle Ages, the drained lakes of the seventeenth century, the increase in scale after 1800, the cases of flooding of the 1990s, the reclamation of the IJsselmeerpolders, the Delta project, and the large-scale projects to improve the river dikes. The role that the Netherlands is playing in the field of water management at the international scene is also being dealt with. The book is supplemented with a list of references, registers and many maps. The richly illustrated Man-made lowlands is intended for those who have an interest for the Netherlands landscape, history of water management and the history of technology.